Sustainable Regional Development Through the Development of Smart Village and Smart Branding: A Case Study of Bangsri Village, Blora Regency - Rachmawati, Rini; Anindya Puteri Eka Susilowati; Prananta Radika; Tria Sofie; Muhammad Yuda Aditya (Jurnal Sistem Cerdas, 2024)
Tourism village development is one of the steps in village development that is now widely pursued, especially for villages with unique potential. However, sustainability is a challenge in the development of tourism villages. This research examines the factors that involved in sustainable regional development through smart village and smart branding. This concept is used because it can accelerate the development of tourism villages. A case study was conducted in Bangsri Village, Blora Regency, Central Java. The factors that involved in the development of smart village and smart branding in Bangsri Village mainly include the initiative and innovation of village leadership, support from local government, community awareness and participation, and tourism branding through the development of landmarks at the Noyo Gimbal View tourist attraction and intensive use of social media. The sustainable regional development strategy is formulated using the SWOT method and elaborated with tourism village development strategy, resulting the following strategy: development of cultural tourism potential, coordination with local government regarding the improvement of road accessibility and enhancement of available amenities, periodic assessment of tourism trends adjusted to village conditions, and empowerment of all community layers, as well as the establishment of regulations governing the management of tourism villages in the future.